Perlakuan Dan Pengujian Pasir Sungai Rokan Hulu Bagian Hilir Untuk Memenuhi Standar Pasir Cetak Pengecoran Logam Alumunium - Apri, Welli; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Riau Province has a very large potential of river sand because there are many rivers, one of them is the Rokan Hulu river. The sand utilization at Rokan Hulu river has not been optimized yet because it is only used as a building material. One of the potential uses of sand of Rokan Hulu river is as a sand mold for metal casting. The purpose of this study is to obtain river sand that meets the sand casting standards on aluminum casting, by providing several treatments such as adding clay content and moisture content. The characteristics of river sand is by measuring the sand distribution, clay content, moisture content, permeability and compression testing. The test results show that the GFN value of the sand at the downstream Rokan Hulu river is 65.64, which means it has the potential to be used as a metal casting sand mold. The addition of 672 gr bentonite, 1172 gr, and 1672 gr produced clay content in the sand to be 10%, 15% and 20%, respectively. The addition of water of 100 gr, 600 gr, and 1100 gr produces water content in sand to 2%, 7%, and respectively. Permeability testing of 9 (nine) sand samples yields maximum and minimum values of 0.0792 cm / min and 0.04668 cm / min, respectively. Keyword: River sand, aluminium casting, clay content, water content, permeability